Establishing a systematic framework to characterise in vitro methods for human hepatic metabolic clearance. (December 2018) - Gouliarmou, Varvara; Lostia, Alfonso Maria; Coecke, Sandra; Bernasconi, Camilla; Bessems, Jos; Dorne, Jean Lou; Ferguson, Stephen; Testai, Emanuela; Remy, Ursula Gundert; Brian Houston, J.; Monshouwer, Mario; Nong, Andy; et al.
Abstract: Hepatic metabolic clearance is one of the most important factors driving the overall kinetics of chemicals including substances used in various product categories such as pesticides, biocides, pharmaceuticals, and cosmetics. A large number of in vitro systems from purified isozymes and subcellular organelles to hepatocytes in simple cultures and in complex scaffold setups are available for measuring hepatic metabolic clearance for different applications. However, there is currently no approach for systematically characterising and comparing these in vitro methods in terms of their design, applicability and performance. To address this, existing knowledge in the field of in vitro human hepatic metabolic clearance methods was gathered and analysed in order to establish a framework to systematically characterise methods based on a set of relevant components. An analogous framework would be also applicable for non-human in vitro systems. The components are associated with the biological test systems used ( e.g. subcellular or cells), the in vitro method ( e.g. number of cells, test item solubility), related analytical techniques, data interpretation methods (based on substrate depletion/metabolite formation), and performance assessments (precision and accuracy of clearance measurements). To facilitate the regulatory acceptance of this class of methods, it is intended that the framework provide the basis of harmonisation work within the OECD. Highlights: Promote the use of toxicokinetic (TK) data to support chemical risk assessment Hepatic metabolic clearance often used as major TK process in chemical risk assessment. Develop a framework to characterise in vitro hepatic metabolic clearance methods Facilitate the regulatory acceptance of in vitro hepatic metabolic clearance data